To coach a killer - Laurie, Victoria (Laurie, Victoria. Life Coach mysteries., 2020)
Cat's efforts to secure her position as East Hampton's premier life coach are complicated by a string of murders that implicate a handsome local bad boy who has made her an unusual offer.